Original Article Clinical Experience on Usage of Apixaban in Thrombosis Management Study (CEATMS): Clinical Experience on Usage of Apixaban in Thrombosis Management Study (CEATMS) (Bombay Hospital Journal, 2024)
Oral anticoagulation therapy (OAT) has been increasing in clinical practice for the prophylaxis and treatment of thromboembolic conditions, such as atrial fibrillation (AF). Warfarin is the standard of care, but its disadvantages include interactions with drugs and food, slow onset of action, and narrow therapeutic index. Non-VKA oral anticoagulants (NOACs) such as dabigatran, rivaroxaban, and apixaban are now approved for prevention of thrombosis in both NVAF and VTE. The aim of the present study is to explicate the use of NOACs in various thromboembolic disorders.
Keywords: Oral anticoagulation therapy, Prophylaxis, Thromboembolic conditions